GENDER INEQUALITY AGAINST WOMEN FISHERS IN INDONESIA - Purwanti, Ani; Wijaningsih, Dyah; Mahfud, Muh. Afif; Natalis, Aga (Indonesia Law Review, 2023)
This study explores whether or not Law No. 7 of 2016 for the Protection and Empowerment of Fishermen, Fish Cultivators, and Salt Farmers discriminates against women. This law supports small fishermen since it requires the government to provide them with financial stability through harvest season output guarantees. On the other hand, we discovered that Law No. 7 of 2016, about the Protection and Empowerment of Fishermen, Fish Cultivators, and Salt Farmers, has discriminatory consequences damaging the welfare of female fishermen. Because of sociological and cultural bias, female fishermen are the most neglected segment in the fishing sector. This is in comparison to other individuals employed in the fishing industry. The Protection and Empowerment of Fishermen, Fish Cultivators, and Salt Farmers Act of 2016 do not recognise or compel affirmative action for women fishermen to have equal access to protection and empowerment programmes. Because the law seeks to protect and empower fishermen, fish farmers, and salt producers, this is the case. This makes it exceedingly challenging for female fishermen, who are already socially expected to remain at home and away from the fishing industry. This type of research is qualitative and collects data using a socio-legal methodology. This approach blends legal research with other types of research, including language and contextual research. People feel that patriarchal societies significantly impact the research topic, despite the fact that this is not a legal issue. The results of this study indicate that Law No. 7 of 2016, Concerning the Protection and Empowerment of Fishermen, Fish Cultivators, and Salt Farmers, Does Not Adequately Regulate the Fulfillment of the Rights of Women Fishermen. This is because the law only addresses the topic of empowerment and does not address the aspect of protection. Because Maritime Affairs and Fisheries Service employees consider fishermen to be ship owners and crews, women in Kendal Regency, who are equivalent to men in the fishermen's insurance plan, are not eligible for fishermen's insurance and hence cannot obtain it.